Psychological group-treatments of social anxiety disorder: a meta-analysis. - Hanna Wersebe (Public Library of Science (PLoS), 2013)
Background A few meta-analyses have examined psychological treatments for a social anxiety disorder (SAD). This is the first meta-analysis that examines the effects of cognitive behavioural group therapies (CBGT) for SAD compared to control on symptoms of anxiety. Method After a systematic literature search in PubMed, Cochrane, PsychINFO and Embase was conducted; eleven studies were identified that met the inclusion criteria. The studies had to be randomized controlled studies in which individuals with a diagnosed SAD were treated with cognitive-behavioural group therapy (CBGT) and compared with a control group. The overall quality of the studies was moderate. Results The pooled effect size indicated that the difference between intervention and control conditions was 0.53 (96% CI: 0.33-0.73), in favour of the intervention. This corresponds to a NNT 3.24. Heterogeneity was low to moderately high in all analyses. There was some indication of publication bias. Conclusions It was found that psychological group-treatments CBGT are more effective than control conditions in patients with SAD. Since heterogeneity between studies was high, more research comparing group psychotherapies for SAD to control is needed.